Trapped in Desired: A Comparative Study of Identity Diffusion in Anna Karenina and Madame Bovary - Zuvyati Aryani Tlonaen; Rohmatul Fitriyah Dewi (OKARA: Jurnal Bahasa dan Sastra, 2025)
Two female characters from different cultural backgrounds, Russia and France, in the novels Anna Karenina and Madame Bovary, demonstrate signs of identity diffusion. This study employs a qualitative content analysis method. The analysis involves close reading of the novels, identifying relevant quotations, classifying the data, and interpreting meanings related to identity issues. Data were collected through documentation by selecting quotations that reflect the characters' identity problems. The research instrument is based on eight indicators of identity diffusion proposed by Kroger and Marcia (2011): lack of exploration, lack of commitment, external influence, lack of self-definition, emotional emptiness, isolation, lack of autonomy from role models, and the need for external validation. The findings reveal that Anna and Emma experience identity diffusion, characterized by unstable self-concepts, emotional dissatisfaction, dependence on others' approval, and failure to develop independent identities. However, the causes of their identity crises differ. Anna's identity diffusion is strongly shaped by social pressure and aristocratic expectations, whereas Emma's is influenced by romantic fantasies and literary idealization. These unresolved conflicts lead both characters to psychological decline and self-destruction. Future researchers are recommended to examine other identity statuses in cross-cultural literary works and explore their relevance to social and psychological issues.